2009
DOI: 10.1253/circj.cj-08-1116
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up of Neointimal Coverage of Sirolimus-Eluting Stents

Abstract: ecent clinical trials have proved that drug-eluting stents (DES) inhibit neointimal proliferation and reduce the risk of in-stent restenosis. 1,2 However, there have been major concerns regarding the potential development of late stent thrombosis related to delayed neointimal formation over the struts of the DES and the discontinuation of dual antiplatelet therapy. 3 Although the incidence of DES thrombosis is reported to be less than 1%, 4-8 the incidence of death or myocardial infarction associated with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 40 publications
1
43
0
3
Order By: Relevance
“…For example, the cause of late-or very-late stent thrombosis after DES implantation during the convalescent phase is not well understood, but recently, late malapposition, uncovered stent struts, and positive vessel remodeling have been identified, by IVUS and OCT analysis, as latent factors after DES implantation. [24][25][26][27][28][29] In the present study, the rate of malapposition and uncovered stent struts in the SES group was significantly higher than in the BMS group. The RESTART study, which examined stent thrombosis after SES implantation, showed that PSS visualized by coronary angiography (suggesting late malapposition) relates to very-late stent thrombosis.…”
Section: Examination Of Stent Coverage By Octmentioning
confidence: 78%
“…For example, the cause of late-or very-late stent thrombosis after DES implantation during the convalescent phase is not well understood, but recently, late malapposition, uncovered stent struts, and positive vessel remodeling have been identified, by IVUS and OCT analysis, as latent factors after DES implantation. [24][25][26][27][28][29] In the present study, the rate of malapposition and uncovered stent struts in the SES group was significantly higher than in the BMS group. The RESTART study, which examined stent thrombosis after SES implantation, showed that PSS visualized by coronary angiography (suggesting late malapposition) relates to very-late stent thrombosis.…”
Section: Examination Of Stent Coverage By Octmentioning
confidence: 78%
“…3,4,10 OCT is an interferometer-based imaging modality that produces a 2-D image of optical scattering from internal tissue microstructures with a high resolution of approximately 10-20 μm, 10-fold higher than that of IVUS. 11- 13 In the present study, we compared OCT with IVUS images in patients with CTEPH during PTPA.…”
Section: Images In Cardiovascular Medicine Tatebe S Et Almentioning
confidence: 99%
“…11) Several studies have investigated the accuracy of quantitative OCT measurements. [12][13][14][15] When OCT was performed in a plexiglass phantom manufactured with a precision of 10 μm, the OCT measurement correlated extremely well with the real luminal dimension (relative standard deviation 1.8%, r = 1.000, intercept 0.01, slope 1.02). 4) In addition, OCT measurement demonstrated a high correlation with IVUS in vivo (R 2 = 0.82, P < 0.001).…”
Section: Discussionmentioning
confidence: 86%